Methanol, a Plugin Marine Fuel for Green House Gas Reduction—A Review - Dimitrios Parris; Konstantinos Spinthiropoulos; Konstantina Ragazou; Anna Giovou; Constantinos Tsanaktsidis (Energies, 2024)
The escalating global demand for goods transport via shipping has heightened energy consumption, impacting worldwide health and the environment. To mitigate this, international organizations aim to achieve complete fuel desulphurization and decarbonization by 50% by 2050. Investigating eco-friendly fuels is crucial, particularly those with a reduced carbon and zero sulfur content. Methanol derived mainly from renewable sources and produced by carbon dioxide’s hydrogenation method, stands out as an effective solution for GHG reduction. Leveraging its favorable properties, global scalability, and compatibility with the existing infrastructure, especially LNGs, methanol proves to be a cost-efficient and minimally disruptive alternative. This review explores methanol’s role as a hybrid maritime fuel, emphasizing its ecological production methods, advantages, and challenges in the shipping industry’s green transition. It discusses the environmental impacts of methanol use and analyzes economic factors, positioning methanol not only as an eco-friendly option, but also as a financially prudent choice for global shipping. Methanol is efficient and cost-effective and excels over MGO, especially in new ships. It is economically advantageous, with decreasing investment costs compared to LNG, while providing flexibility without specialized pressure tanks. Global marine fuel trends prioritize fuel traits, accessibility, and environmental considerations, incorporating factors like policies, emissions, bunkering, and engine adaptability during transitions.